Methylphenidate enhances implicit learning in healthy adults - Klinge, C; Shuttleworth, C; Muglia, P; Nobre, A; Harmer, C; Murphy, S (SAGE Publications, 2017)
Background and Purpose. One limiting factor in the development of pharmacological interventions to enhance cognition is the absence of biomarkers that can be used in healthy volunteers to screen novel compounds. Drug discovery has tended to rely heavily on explicit measures of cognition, but these are typically insensitive to cognition enhancing effects in healthy volunteers. This study investigated whether a novel battery of implicit cognition measures is sensitive to the effects of methylphenidate (Ritalin) in healthy volunteers. Experimental Approach. 80 healthy volunteers were randomised to receive either a single (10mg) dose of methylphenidate or matched placebo. Participants completed a battery of tasks measuring implicit cognition (location priming, contextual cueing, implicit task switching). The effect of methylphenidate on standard, explicit measures of cognition was also assessed. Key Results. Methylphenidate enhanced implicit learning on the location priming task and the implicit task-switching task. In line with previous work, we found these effects were greater in male volunteers. There was no evidence for improved learning in any of the explicit measures. Conclusion and Implications. These results demonstrate that implicit measures of cognition are sensitive to pharmacological interventions in healthy volunteers. As such, implicit cognition measures may be a useful way of screening and tracking cognitive effects of novel agents in experimental medicine studies.